1991
DOI: 10.1021/bi00240a018
|View full text |Cite
|
Sign up to set email alerts
|

Human fibroblast stromelysin catalytic domain: expression, purification, and characterization of a C-terminally truncated form

Abstract: Stromelysin-1 is a member of a tissue metalloproteinase family whose members are all capable of degrading extracellular matrix components. A truncated form of human fibroblast prostromelysin 1 lacking the C-terminal, hemopexin-like domain has been expressed in Escherichia coli and purified to homogeneity. Treatment of this short form of prostromelysin with (aminophenyl)mercuric acetate resulted in activation and loss of the propeptide in a manner identical with the wild-type, full-length protein. Kinetic compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 38 publications
4
66
0
Order By: Relevance
“…Since inhibition of PMNL collagenase and Mr,40000 fragment with TIMP-1 or rTIMP-2 demonstrated similar Kd values, it may be concluded that the C-terminal domain of PMNL collagenase does not contribute to the binding reaction of both matrix metalloproteinase inhibitors. (Chin et al, 1985;Okada et al 1986;Clark and Cawston, 1989;Marcy et al, 1991;. Autoproteolysis of all these enzymes, including the PMNL collagenase, takes place in a proline-rich region, which is possibly a hinge region between the catalytic and C-terminal domains.…”
Section: Ii-g-p-q-t-p-k-mentioning
confidence: 99%
“…Since inhibition of PMNL collagenase and Mr,40000 fragment with TIMP-1 or rTIMP-2 demonstrated similar Kd values, it may be concluded that the C-terminal domain of PMNL collagenase does not contribute to the binding reaction of both matrix metalloproteinase inhibitors. (Chin et al, 1985;Okada et al 1986;Clark and Cawston, 1989;Marcy et al, 1991;. Autoproteolysis of all these enzymes, including the PMNL collagenase, takes place in a proline-rich region, which is possibly a hinge region between the catalytic and C-terminal domains.…”
Section: Ii-g-p-q-t-p-k-mentioning
confidence: 99%
“…Indeed, the C domain alone of collagenase-1 binds native type I collagen (32)(33)(34), as can the C domain of stromelysin-1 (33,34), even though collagen is not cleaved by stromelysin-1. In contrast, neither the activity nor the substrate specificity of the stromelysins is dramatically modified by the removal of the C domain (35)(36)(37)(38). Likewise, the gelatinases degrade gelatin and native type IV collagen in a manner that appears independent of the presence of the C domain (39).…”
mentioning
confidence: 99%
“…They all consist of a propeptide and a catalytic domain followed by a hemopexin-like domain, which is coupled by a hinge region to the first two domains [15]. PMNL coilageaase contains three eysteine residues° with two of them believed to be disulfide bridged in the hemopexinlike domain and one unbridged in the propeptide domain.…”
Section: Resultsmentioning
confidence: 99%